2013
DOI: 10.1080/03055698.2012.681360
|View full text |Cite
|
Sign up to set email alerts
|

The decision-making and changing behavioural dynamics of potential higher education students: the impacts of increasing tuition fees in England

Abstract: The decisionmaking and changing behavioural dynamics of potential higher education students: the impacts of increasing tuition fees in England. Educational Studies, 39(2), pp.125-141. Education Studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 47 publications
(55 reference statements)
2
68
0
7
Order By: Relevance
“…This finding lends support to many previous studies that financial cost continues to be an important factor in students' choice of institution for master's programmes (e.g., Sidin, Hussin, & Soon, 2003;Paulsen & St John, 2002;Wilkins, Shams, & Huisman, 2013). Consistent with this study's finding, Sidin, Hussin and Soon (2003) found that in Malaysia income affects the choice of students along the public-private education divide.…”
Section: Int3supporting
confidence: 82%
See 1 more Smart Citation
“…This finding lends support to many previous studies that financial cost continues to be an important factor in students' choice of institution for master's programmes (e.g., Sidin, Hussin, & Soon, 2003;Paulsen & St John, 2002;Wilkins, Shams, & Huisman, 2013). Consistent with this study's finding, Sidin, Hussin and Soon (2003) found that in Malaysia income affects the choice of students along the public-private education divide.…”
Section: Int3supporting
confidence: 82%
“…Much of our understanding in college choice factors has been enhanced by research conducted in developed countries (e.g., Briggs, & Wilson, 2007;Nurnberg, Schapiro, & Zimmerman, 2012;Liu, 2005;Vrontis, Thrassou, & Melanthiou, 2007;Wilkins, Shams, & Huisman, 2013). In this regard, Liu (2005) observed that, "Most of the studies in college choice were conducted in the United States, Australia and some European countries" (p. 18).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Wilkins et al's (2013) study of English high school students, just before the 2012/13 reforms, uncovers "an increasing anxiety about financial issues" (136) but no evidence that low-income students are more likely to be deterred from higher education entry because of the costs and debts involved. They reason that higher education entry is gradually becoming the norm for students from various social backgrounds, so "students from working class backgrounds may feel compelled not to lose out and therefore opt to enroll" (Wilkins et al 2013, 12).…”
Section: Prospective Students' Attitudes Toward Debtmentioning
confidence: 99%
“…Pennell and West, 2005;Jones and Thomas, 2005;Callender, 2012;Wilkins et al, 2013). It is generally argued that an underlying fear of debt discourages people from applying to university, especially those from lower socio-economic groups and others with a stronger aversion towards borrowing (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%